ChemInform Abstract: Simple and Cost Effective Acid Catalysts for Efficient Synthesis of 9‐Aryl‐1, 8‐dioxooctahydroxanthene. Issue 22 (13th May 2013) - Ilangovan, A.; Muralidharan, S.; Sakthivel, P.; Malayappasamy, S.; Karuppusamy, S.; Kaushik, M. P.
Abstract The condensation of dimedone with aromatic aldehydes can be catalyzed by CaCl2 or HBr.